Defining the Joint Cost in the Field of CSR and Disclosing it in the Financial Statements: An Initiative to Enrich the Thought of Accounting for CSR - Saleh, Younis A. Battal (The International Journal of Accounting and Business Society, 2023)
Purpose: This study aims to establish a precise definition of the term ʺjoint costʺ in the field of CSR and discuss the issues of disclosing this cost in the financial statements. Method: To raise a meaningful discussion about the meaning of joint cost in the field of CSR, through which an accurate definition can be developed regarding it, this study adopted the following concepts: 1) Overlapping CSRs; 2) The real sacrifice; 3) Independent legal personality; 4) Untargeted social or economic benefits; 5) Mixed costs resulting from loaning fixed assets and providing non-material assistance such as advisory services, construction and maintenance works, etc. By adopting the possible behavior method and supporting justifications, the researcher will discuss all expected scenarios regarding disclosing these costs in the financial statements. Result: This study developed a precise definition of the term ″joint cost″ ′′ in the field of CSR. It also provided a meaningful discussion on the issues of disclosing this cost in reports and financial statements. Also, this study identified three basic principles for achieving transparency when disclosing charitable activities, including a joint cost. Originality /Value: This study is considered an enrichment of accounting thought in the field of CSR. It will enhance companies' capabilities in adequately and transparently disclosing their commitment to CSR. Also, this study is considered an invitation to international accounting organizations to issue recommendations regarding how to disclose in the financial statements about charitable activities, especially those that reflect the concept of joint cost or whose costs are small but produce great benefits.